Ukraiński ruch filmowy we Lwowie w latach 30. XX wieku - Gierszewska, Barbara Lena (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2023)
Title of the article: The Ukrainian film movement in 1930s Lviv The Ukrainian film movement in the 1930s was not developed on a wider scale. Due to the cost of the equipment and the film, few people could make films. Those who did included the members of the Ukrainian Photographic Society, who had completed specialist film courses. Their achievements included short feature films and documentary films, some of which were of true artistic merit. From the circle of Ukrainian cinematographers, J. Dorosz, S. Kułykiwna, W. Humecki and J. Bochenski deserve mention special. Moreover, the last two film-makers wrote about the necessity of recording Ukrainian cultural heritage; they expressed the need for patriotic, socially useful films. At that time, Ukrainian film criticism also developed in Lviv, In particular, it found expression in two outstanding periodicals published in the Ukrainian language, “Cinema” (1930–1936) and “Light and Shadow” (1933–1939).